Screening for Postpartum Depression and Associated Factors Among Women in China: A Cross-Sectional Study - Chi, Xinli; Zhang, Peichao; Wu, Haiyan; Wang, Jian (Frontiers in Psychology, 2016)
Abstract Abstract Objectives: This study examined what percentage of Chinese mothers during a three-year postpartum period were screened for postpartum depression and explored the correlation between postpartum depression and various socio-demographic, psychological, and cultural factors. Study design: Cross-sectional survey. Methods: A total of 506 mothers 23 years of age and older who were within three years postpartum completed the online survey. The survey collected information such as family economic status, a history of depression, preparation for pregnancy, relationships with husbands and family members, adult attachment types (Adult Attachment Scale, AAS), and depression (The Center for Epidemiologic Studies Depression Scale, CESD). Results: Approximately 30% of mothers 1–3 years postpartum reported symptoms above the CESD cut-off score (≥16 scores) associated with the risk for depression (28.0% in the first year, 30.8% in the second year, and 31.8% in the third year). Factors significantly associated with depression in participants in the correlation analysis were education level; family income; preparation for pregnancy; a history of depression; amount of time spent with their husbands; relationships with husbands, parents, and parents-in-law; and a close, dependent, and/or anxious attachment style. Multiple regression analyses revealed that a history of depression; less preparation for pregnancy; poorer relationships with husbands, parents, and parents-in-law; and a more anxious attachment style were strongly related to a higher risk of postpartum depression. Conclusions: The overall percentage of mothers after delivery who were vulnerable to depression in China remains high. Various factors were significant predictors of postpartum depression. The research findings have several valuable implications for intervention practices. For example, attachment styles and depression history in the assessments of perinatal depression could improve screenings and the design of interventions. Additionally, improving the family relationships and family environments of women post-delivery may be promising approach for postpartum depression prevention or intervention. Keywords: postpartum depression, postnatal depression, prevalence, correlates, adult attachment